Quantifying intra‐ and inter‐fractional motion in breast radiotherapy. Issue 1 (13th July 2014) - Jones, Scott; Fitzgerald, Rhys; Owen, Rebecca; Ramsay, Jonathan
<x xml:space="preserve">Abstract</x> An investigation into the magnitude of intra‐ and inter‐fractional motion variation present in the set up of breast cancer patients receiving radiotherapy. Variation was greatest inter‐fractionally but still within tolerance. This review of the breast technique provides confidence in our set up and the ability to move towards advanced treatment techniques. <boxed-text content-type="graphic" id="jmrs61-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>